2019
DOI: 10.1111/epi.15665
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of hemimegalencephaly into the phenotypic spectrum of NPRL3 pathogenic variants in familial focal epilepsy with variable foci

Abstract: Despite tremendous progress through next generation sequencing technologies, familial focal epilepsies are insufficiently understood. We sought to identify the genetic basis in multiplex Palestinian families with familial focal epilepsy with variable foci (FFEVF). Family I with 10 affected individuals and Family II with five affected individuals underwent detailed phenotyping over three generations. The phenotypic spectrum of the two families varied from nonlesional focal epilepsy including nocturnal frontal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
(67 reference statements)
3
23
0
Order By: Relevance
“… 11 FCD type II is the most common MCD seen in GATOR1-related epilepsies. 9–11 , 30 , 61 , 63 FCD type I, 11 , 30 , 36 BOSD, 26 , 61 , 121 HME, 31 , 122 polymicrogyria 4 and subcortical band heterotopia 121 have also been reported in individuals with GATORopathies ( Table 3 ). Cognitive comorbidities are seen in approximately half of affected individuals and psychiatric disorders observed in over 40% of cases.…”
Section: Personalized Medicine In Mtoropathy-related Epilepsiesmentioning
confidence: 99%
“… 11 FCD type II is the most common MCD seen in GATOR1-related epilepsies. 9–11 , 30 , 61 , 63 FCD type I, 11 , 30 , 36 BOSD, 26 , 61 , 121 HME, 31 , 122 polymicrogyria 4 and subcortical band heterotopia 121 have also been reported in individuals with GATORopathies ( Table 3 ). Cognitive comorbidities are seen in approximately half of affected individuals and psychiatric disorders observed in over 40% of cases.…”
Section: Personalized Medicine In Mtoropathy-related Epilepsiesmentioning
confidence: 99%
“…The proposed pathogenic mechanism of the NPRL3 gene mutation is that LOF causes an haploinsufficiency induced by nonsense-mediated decay of mRNA as previously suggested that truncating mutations in NPRL3 reduce transcript levels significantly (Canavati et al, 2019). In this study, we found a nonsense mutation c.316C>T, p. Gln106* in the NPRL3 gene, which is located in exon4 (Figure 2).…”
Section: Disscussionsupporting
confidence: 60%
“…For example, some NPRL3 c.349delG heterozygotes develop seizures, while others will not (overall, seizure penetrance was estimated at 28%). In patients with epilepsy, MRI findings revealed a spectrum ranging from no visible abnormalities to hemimegalencephaly, ours being the second reported case of hemimegalencephaly associated with a pathogenic NPRL3 variant 9 . Surprisingly, the most severe seizure phenotypes were not always observed in patients with the most abnormal MRIs and in some individuals with seizures, brain MRI was normal.…”
Section: Discussionmentioning
confidence: 60%
“…Focal cortical dysplasia II (FCDII) is an MCD highly associated with intractable seizures defined by disorganized cerebral cortical lamination, enlarged (cytomegalic) dysmorphic neurons, and heterotopic neurons in the white matter 3 . Variants in genes encoding components of the GTPase Activating Protein (GAP) Activity Towards Rags Complex 1 (GATOR1), including DEP domain containing 5 (DEPDC5), Nitrogen Permease Regulator Like 2 (NPRL2), and Nitrogen Permease Regulator Like 3 (NPRL3) [4][5][6] , are the most common MPG variants associated with FCDII 7 and hemimegalencephaly (HME), a MCD defined by a hemispheric enlargement and FCD-type II histopathology 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation